COMPARASION OF FINANCIAL FAILURE PREDICTION MODELS: AN APPLICATION IN BIST FOOD AND BEVERAGE SECTOR (Third Sector Social Economic Review, 2025)
In times of crises and possible economic recessions, the importance of the financial structures of the enterprises to avoid losses or to continue their activities with the least loss reveals the importance of their financial structures. Predetermining financial failure is important for the future of businesses in an increasingly competitive environment and helps companies maintain their strength in the competitive environment and focus on their long-term goals. This study aims to calculate the financial failures of enterprises operating in the BIST Food sector, aiming to achieve financial success and contribute to the economy, with the help of prediction models, to compare their results and to investigate whether they are financially successful or unsuccessful. In this direction, the annual financial data of the enterprises whose stocks are traded in the BIST Food and Beverage sector for the period 2015-2022 are used and Altman Z'' Score, Fulmer H Score and Springate S Score methods were used to analyze financial failure. As a result of the study, the financial failure prediction rates of the models were determined. According to the results of the analysis; Altman Z The score financial failure rate is 13%, the Springate S score financial failure rate is 44%, and the Fulmer H score financial failure prediction rate is 6% based on 170 data after removing 30 data that cannot be calculated.
Keywords: Financial failure; Prediction models; Altman z score; Fulmer h score; Springate s score